2022
DOI: 10.1007/s10989-022-10450-w
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Delta Variant is Recognized Through GRP78 Host-Cell Surface Receptor, In Silico Perspective

Abstract: Different SARS-CoV-2 new variants emerged and spread during the past few months, sparking infections and death counts. The new variant B.1.617 (delta variant) sparked in India in the past few months, causing the highest records. The B.1.617 variant of SARS-CoV-2 has the double mutations E484Q and L452R on its spike Receptor Binding Domain (RBD). The first mutation is like the reported South African and the Brazilian variants (501.V2 and B.1.1.248). This mutation lies in the region C480-C488, which we predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…On the other hand, the ACE2 ( Figure 2 D) shows almost the same binding affinity against the WT and variant RBDs (-10.02 up to 11.60 kcal/mol), which are higher than that for GRP78. This coincides with the fact that ACE2 is the main recognition element and Cs-GRP78 is an auxiliary recognition site for SARS-CoV-2 ( 2 , 10 ).
Figure 2 (A) The root-mean-square deviation (RMSD) of the WT (black) and the mutated variants RBDs (alpha: orange, beta or gamma: gray, delta: yellow, delta+: cyan, lambda: green, C36: blue, and omicron: brown) versus the simulation time in ns.
…”
Section: Binding Affinities Of the Grp78 And Ace2 To Different Rbdssupporting
confidence: 80%
“…On the other hand, the ACE2 ( Figure 2 D) shows almost the same binding affinity against the WT and variant RBDs (-10.02 up to 11.60 kcal/mol), which are higher than that for GRP78. This coincides with the fact that ACE2 is the main recognition element and Cs-GRP78 is an auxiliary recognition site for SARS-CoV-2 ( 2 , 10 ).
Figure 2 (A) The root-mean-square deviation (RMSD) of the WT (black) and the mutated variants RBDs (alpha: orange, beta or gamma: gray, delta: yellow, delta+: cyan, lambda: green, C36: blue, and omicron: brown) versus the simulation time in ns.
…”
Section: Binding Affinities Of the Grp78 And Ace2 To Different Rbdssupporting
confidence: 80%
“…With the rapid emergence of SARS-CoV-2 variants that have mutations in the spike protein that present challenges to the current vaccine strategy, there is an urgent need to identify cellular targets and therapeutics that can bypass these obstacles. Interestingly, recent computational analyses revealed that GRP78 could bind to the SARS-CoV-2 spike from different variants, including alpha, beta, delta, delta+, lambda, C36, and Omicron [ 32 , 33 ], suggesting that, in targeting GRP78, a critical host cell co-receptor may be effective in fighting the pandemic. Here, consistent with the computer modeling predictions, we demonstrated the effectiveness of the GRP78 inhibitor, YUM70, in blocking the entry of pseudo-viral particles bearing different variants of the SARS-CoV-2 spike protein.…”
Section: Discussionmentioning
confidence: 99%
“…This variant, which has evolved to become the predominant genotype worldwide, can evade cellular immunity, have high infectivity, and increase host glycolysis and fusogenicity, increasing the number of hospitalized patients with high morbidity and mortality. 38 , 39 These mutations also had the potential to evade the protective antibodies derived from the convalescent sera or vaccine origin, as well as those used in therapy, which could favor virus expansion and compromise infection control. 40 The results of a study have revealed a set of mutations, such as D614G and P314L, that influence the outcomes of SARS-CoV-2 infection and guide the development of SARS-CoV-2 vaccines.…”
Section: Discussionmentioning
confidence: 99%